Simiate is an Actin binding protein involved in filopodia dynamics and arborization of neurons - Derlig, Kristin; Ehrhardt, Toni; Gießl, Andreas; Brandstätter, Johann H.; Enz, Ralf; Dahlhaus, Regina (Frontiers in Cellular Neuroscience, 2014)
The Actin cytoskeleton constitutes the functional base for a multitude of cellular processes extending from motility and migration to cell mechanics and morphogenesis. The latter is particularly important to neuronal cells since the accurate functioning of the brain crucially depends on the correct arborisation of neurons, a process that requires the formation of several dozens to hundreds of dendritic branches. Recently, a model was proposed where different transcription factors are detailed to distinct facets and phases of dendritogenesis and exert their function by acting on the Actin cytoskeleton, however, the proteins involved as well as the underlying molecular mechanisms are largely unknown. Here, we demonstrate that Simiate, a protein previously indicated to activate transcription, directly associates with both, G- and F-Actin and in doing so, affects Actin polymerisation and Actin turnover in living cells. Imaging studies illustrate that Simiate particularly influences filopodia dynamics and specifically increases the branching of proximal, but not distal dendrites of developing neurons. The data suggests that Simiate functions as a direct molecular link between transcription regulation on one side, and dendritogenesis on the other, wherein Simiate serves to coordinate the development of proximal and distal dendrites by acting on the Actin cytoskeleton of filopodia and on transcription regulation, hence supporting the novel model.